Professional SharePoint 2013 development - Alirezaei, Reza; Schwartz, Brendon; Ranlett, Matt; Hillier, Scot; Wilson, Brian; Fried, Jeff; Swider, Paul (Wiley, 2013)
Thorough coverage of development in SharePoint 2013 A team of well-known Microsoft MVPs joins forces in this fully updated resource, providing you with in-depth coverage of development tools in the latest iteration of the immensely popular SharePoint. From building solutions to building custom workflow and content management applications, this book shares field-tested best practices on all aspect of SharePoint 2013 development. Offers a thorough look at Windows Azure and SharePoint 2013Includes new chapters on Application Life Cycle Management, developing apps in ShareP.